Airborne protein concentration: a key metric for type 1 allergy risk assessment—in home measurement challenges and considerations. Issue 1 (26th March 2018) - Tulum, Liz; Deag, Zoë; Brown, Matthew; Furniss, Annette; Meech, Lynn; Lalljie, Anja; Cochrane, Stella
Abstract: Background: Exposure to airborne proteins can be associated with the development of immediate, IgE‐mediated respiratory allergies, with genetic, epigenetic and environmental factors also playing a role in determining the likelihood that sensitisation will be induced. The main objective of this study was to determine whether airborne concentrations of selected common aeroallergens could be quantified in the air of homes using easily deployable, commercially available equipment and analytical methods, at low levels relevant to risk assessment of the potential to develop respiratory allergies. Additionally, air and dust sampling were compared and the influence of factors such as different filter types on allergen quantification explored. Methods: Low volume air sampling pumps and DUSTREAM ® dust samplers were used to sample 20 homes and allergen levels were quantified using a MARIA ® immunoassay. Results: It proved possible to detect a range of common aeroallergens in the home with sufficient sensitivity to quantify airborne concentrations in ranges relevant to risk assessment (Limits of Detection of 0.005–0.03 ng/m 3 ). The methodology discriminates between homes related to pet ownership and there were clear advantages to sampling air over dust which are described in this paper. Furthermore, in an adsorption–extraction study, PTFE (polytetrafluoroethylene) filters gave higher and more consistent recovery values than glass fibre (grade A) filters for the range of aeroallergens studied. Conclusions: Very low airborne concentrations of allergenic proteins in home settings can be successfully quantified using commercially available pumps and immunoassays. Considering the greater relevance of air sampling to human exposure of the respiratory tract and its other advantages, wider use of standardised, sensitive techniques to measure low airborne protein concentrations and how they influence development of allergic sensitisation and symptoms could accelerate our understanding of human dose–response relationships and refine our knowledge of thresholds of allergic sensitisation and elicitation via the respiratory tract.